After God: Practical theology as public Christology from the margins of the market - Meylahn, Johann-Albrecht (HTS teologiese studies, 2015)
This article is part of a research project, Conversations after God. The focus of this article is to reflect on the theory and methodology of practical theology in a post-metaphysical (After God) context. It will be suggested that practical theology can redefine itself as public theology, but specifically as Christology by engaging the public texts within their contexts, but from a Christ-science hermeneutical approach. The proposed approach is a hermeneutical approach where the Christ-Ereignis guides the inner- and inter-textual reading of texts within contexts. This Christ-Ereignis cannot be translated into a science or even a definable philosophy and therefore the logos is crossed out. Christology, as public theology is done from the margins of the dominant discourses and therefore it could be seen as a Christology from the margins of the market to create spaces of kingdom life: life in fullness.